2003
DOI: 10.1046/j.1365-2362.2003.01243.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma angiopoietin‐1, angiopoietin‐2 and Tie‐2 in breast and prostate cancer: a comparison with VEGF and Flt‐1

Abstract: Abnormal levels of Ang-1, Ang-2 and their receptor, Tie-2, are present in breast and prostate cancer, and their interrelationships may be important in the pathophysiology of these conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
58
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 71 publications
(45 reference statements)
8
58
0
1
Order By: Relevance
“…There are a few studies on serum Ang-1 levels, and these have reported conflicting results. Compared with the level in controls, the serum Ang-1 level was elevated in breast cancer [25] but lower in thyroid cancer [26]; the level was similar to the control level in prostate cancer [25] and acute myeloid leukemia [27].…”
Section: Introductionmentioning
confidence: 50%
See 2 more Smart Citations
“…There are a few studies on serum Ang-1 levels, and these have reported conflicting results. Compared with the level in controls, the serum Ang-1 level was elevated in breast cancer [25] but lower in thyroid cancer [26]; the level was similar to the control level in prostate cancer [25] and acute myeloid leukemia [27].…”
Section: Introductionmentioning
confidence: 50%
“…In that report, thyroid cancer patients had lower serum Ang-1 and higher serum Ang-2 levels compared with controls, although the prognostic significance was not evaluated. However, an earlier study found variable serum Ang-1 levels according to different types of cancers [25]. In tissue studies, Ang-1 is upregulated in various malignancies, with a few exceptions [22,29,38].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We also confirm raised VEGF and vWf in this disease although we failed to find raised angiopoietin-2. [15][16][17] Notably, in the two control groups, HO-1 correlated with VEGF but in prostate cancer they failed to correlate. Despite considerable animal data, wherein there are indications of various roles of HO-1 in cancer and cardiovascular disease, the role of HO-1 in actual human disease is unclear.…”
Section: Discussionmentioning
confidence: 91%
“…We tested our hypotheses in a simple cross-sectional case-control study of early prostate cancer as this disease is known to be associated with raised markers of angiogenesis and endothelial damage/dysfunction. [15][16][17] …”
Section: Introductionmentioning
confidence: 99%